2023
DOI: 10.1039/d2tc04715b
|View full text |Cite
|
Sign up to set email alerts
|

Advances in circularly polarized luminescence materials based on helical polymers

Abstract: Helical polymers are widely used in chiral recognition, chiral response, asymmetric catalysis, photoelectric functional materials and other fields due to their unique helical structure and optical activity. In recent years,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 93 publications
0
28
0
Order By: Relevance
“…50−54 Interesting phenomena such as the "chiral amplification effect" and "majority rules" further enable chiral helical polymers to become excellent candidates for constructing CPL materials. 55,56 In our previous studies, we have prepared CPL-active chiral helical polyacetylenes with high g lum values up to 10 −1 , which proves the feasibility of fabricating CPL materials based on chiral helical polymers. 57 Moreover, we have found that chiral helical polymers can serve as handed-selective fluorescence filters to transform achiral fluorescence into circularly polarized light even in the absence of any covalent bond or noncovalent bond interaction between chiral components and fluorescent components.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…50−54 Interesting phenomena such as the "chiral amplification effect" and "majority rules" further enable chiral helical polymers to become excellent candidates for constructing CPL materials. 55,56 In our previous studies, we have prepared CPL-active chiral helical polyacetylenes with high g lum values up to 10 −1 , which proves the feasibility of fabricating CPL materials based on chiral helical polymers. 57 Moreover, we have found that chiral helical polymers can serve as handed-selective fluorescence filters to transform achiral fluorescence into circularly polarized light even in the absence of any covalent bond or noncovalent bond interaction between chiral components and fluorescent components.…”
Section: Introductionmentioning
confidence: 63%
“…To achieve C-dots-based CPRTP materials, selecting an appropriate chiral source and building an efficient chirality transfer process from the chiral source to the C-dots are necessary. The stereohelical structure endows chiral helical polymers with a high level chirality and intense optical activity unmatched by small molecules. Interesting phenomena such as the “chiral amplification effect” and “majority rules” further enable chiral helical polymers to become excellent candidates for constructing CPL materials. , In our previous studies, we have prepared CPL-active chiral helical polyacetylenes with high g lum values up to 10 –1 , which proves the feasibility of fabricating CPL materials based on chiral helical polymers . Moreover, we have found that chiral helical polymers can serve as handed-selective fluorescence filters to transform achiral fluorescence into circularly polarized light even in the absence of any covalent bond or noncovalent bond interaction between chiral components and fluorescent components .…”
Section: Introductionmentioning
confidence: 76%
“…The constructed zwitterionic hybrid, [(R/S-3-quinuclidinol•H)MnBr 3 ], can reach both a relatively high g lum value (0.023) and a PLQY of 67%. [29] In this work, to construct more efficient Mn(II)-based CPL emitters with simultaneously high g lum and PLQY parameters, we have applied the helicity design strategy [30] for the first time to Mn(II)-organic CPL emitters. It should be emphasized that chiral metal-organic spirals showing CPL were observed only in a few of Eu(III), [31,32] Ag(I), [33] and Zn(II) [34,35] polymers.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, the research on chiral polymers with CPL activity is still in its infancy. 4,5 Moreover, the related research mainly focuses on nonporous linear polymers, in which aggregation-caused quenching (ACQ) is usually unavoidable in the solid state. Therefore, the development of porous polymer materials with CPL activity is of great scientific significance and application value.…”
mentioning
confidence: 99%
“…9 However, successful examples remain relatively rare for the chemical resolution of racemates. 9,10 Chiral tartaric acid derivatives and 1,1 0 -bi-2,2 0 -naphthol (BINOL) are often used in the chemical resolution of racemic spirocyclic or fused polycyclic diones, such as spiro [4,4]nonane-1,6-dione and 2,3 : 6,7-dibenzobicyclo[3.3.1]nona-2,6-diene-4,8-dione. 10 However, we found that chiral BINOL and tartaric acid derivatives were not suitable for the chemical resolution of 1,1 0 -spirobisindane-3,3 0 -dione.…”
mentioning
confidence: 99%